THE NOTION OF BIG DATA AND ITS LEGAL ASPECTS - Sarvar Tojiboyev (PT. Antis International Publisher, 2025)
Objective: The objective of this study is to highlight the rapid growth of data generated by society through the widespread use of the Internet and the need for new technologies to process large volumes of information. The paper examines how commercial organizations, especially giant companies with access to advanced technologies, have an advantage in data processing, while smaller organizations struggle to compete. Method: The paper reviews the IDC report,